Pendayagunaan Software Asisten Dalam Pengelolaan Sistem Informasi Manajemen Keuangan Sekolah - Iqbal Bukhori; Imas Siti Rojab; Iwan Sopwandin; Ara Hidayat (Universitas Djuanda, 2020)
This study aims to determine the management of the school's financial management system in Madrasah Aliyah Al-mu'awanah and the implementation of Assistant software utilization in the management of the school's financial management system in Al-Mu'awanah Madrasah. This research uses an approach to research and development (R & D) research. Research results show that in practice financial management in Madrasah Aliyah Al-mu'awanah is still based on a manual input data system so that in the process there are obstacles especially in data processing and school financial data recapitulation. Implementation of the use of assistant software in the process of school financial information management provides a positive picture, the statement is reinforced by the presence of a good response from respondents. Based on the distribution of the questionnaire that has been given to the respondents, the percentage of eligibility is 84%. The percentage of feasibility obtained shows that the utilization of computerized software or financial software is feasible to be used as school financial administration software, especially in Madrasah Aliyah Al-Mu'awanah.